West and Central African NARS accelerate climate-smart agriculture scaling using AICCRA and CGIAR knowledge and tools - Segnon, Alcade; Zougmore, Robert (2025)
Building on AICCRA-designed capacity development program on Climate-Smart Agriculture (CSA) to National Agricultural Research Systems (NARSs) in West and Central Africa (WCA), AICCRA regional partner CORAF and the ECOWAS Regional Agency for Food and Agriculture (RAAF) implemented CSA capacity-building initiatives. Harnessing AICCRA and CGIAR tools and knowledge, these initiatives have capacitated 565 people - 123 women- from 19 countries across WCA on CSA concepts, approaches and tools for assessing and scaling CSA technologies, enabling conditions for scaling CSA technologies and innovations.